A CASE OF DEVELOPMENT OF EXTRACAPILLAR SCHONLEIN-HENOCH NEPHRITIS IN 8-YEARS-OLD CHILD WITH IGA-NEPHROPATHY AND NEPHROTIC SYNDROME - N.N. Kartamysheva; A.N. Tsygin (Union of pediatricians of Russia, 2009)
.